Improving Communication Between Pair Programmers Using Shared Gaze Awareness - D'Angelo, Sarah; Begel, Andrew (Proceedings of CHI 2017, 2017)
Remote collaboration can be more difficult than collocated collaboration for a number of reasons, including the inability to easily determine what your collaborator is looking at. This impedes a pair’s ability to efficiently communicate about on-screen locations and makes synchronous coordination difficult. We designed a novel gaze visualization for remote pair programmers which shows where in the code their partner is currently looking, and changes color when they are looking at the same thing. Our design is unobtrusive, and transparently depicts the imprecision inherent in eye tracking technology. We evaluated our design with an experiment in which pair programmers worked remotely on code refactoring tasks. Our results show that with the visualization, pairs spent a greater proportion of their time concurrently looking at the same code locations. Pairs communicated using a larger ratio of implicit to explicit references, and were faster and more successful at responding to those references. Video: